Popular Diets: Raw Foods - Alexa Barad; Daniela Rivero-Mendoza; Wendy J. Dahl (EDIS)
The raw foods diet has its roots in a vegetarian movement dating back to the 1800s. As the name implies, a raw foods diet is a dietary pattern composed of mostly or completely raw, unprocessed foods. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department explores the potential health benefits and risks of a raw foods diet. Written by Alexa Barad, Daniela Rivero-Mendoza, and Wendy Dahl. https://edis.ifas.ufl.edu/fs404